Preventive Effect of Vitamin D in Treatment Management of Intracranial Aneurysm. (16th November 2020) - Kashefiolasl, Sepide; Leisegang, Matthias; Helfinger, Valeska; Schürmann, Christoph; Al-Maawi, Sarah; Ghanaati, Shahram; Hintereder, Gudrun; Badenhoop, Klaus; Senft, Christian; Seifert, Volker; Schröder, Katrin; Brandes, Ralf; et al.
Abstract: INTRODUCTION: Unruptured intracranial aneurysm (UIA) poses a therapeutic dilemma in which the risk-benefit analysis of invasive intervention has to be balanced against the natural history of the disease. To date, there is no medical treatment to prevent aneurysm development, growth and subsequent progression to rupture. METHODS: 25-vitaminD3 levels tested between 2008–2016 and data of SAH patients admitted during the months with a peak versus nadir of VitD3-values were analyzed, retrospectively. We prospectively correlated VitD3 with size and number of aneurysms at the rupture time in patients admitted between 2017–2019. An experimental mice shear stress model and cell culture model were used to investigate the effect of 1, 25-dihydroxy-vitaminD3 (1, 25-VitD3) and acting mediators in this mechanism. RESULTS: Based on the retrospective analysis demonstrating an increased frequency of aneurysm rupture rate in patients during the low vitamin D period in winter, we started the prospective study evaluating plasma vitamin D levels at admission. Number of aneurysms was significantly associated with sufficient plasma Vitamin D level as an independent factor in a multivariate analysis. From bedside back to bench, active 1, 25-VitD3 hormone attenuated the natural history of remodeling in mice basilar artery. Deletion of the vitamin-D-receptor in myeloid cells decreased the protective 1, 25-VitD3 effect. Cell-culture of vascular fibroblasts confirmed the anti-tissue remodeling effect of 1, 25-VitD3. CONCLUSION: 1, 25-VitD3 attenuates collagen remodeling and prevents aneurysm development. However, VitD-administration should be tested as optional treatment in management of patients with UIA.